Potret Penerapan Pemotongan, Penyetoran dan Pelaporan PPH Pasal 23 Atas Jasa Teknik (Studi Kasus Pada PT XXX Madura) - Faraka, Fainsanu; Ferdinan Rasya Saputra, Baqrul; Wahyudi, Bonang; Yanfi Aula Rizqi, Ahmad; Anshin Wifaqi, Yazid; Taufikur Rohman, Mohammad (Journal of Accounting and Finance Management, 2024)
This research aims to analyze the practice of withholding and reporting Income Tax (PPh) 23. regarding installation and electricity pole installation services at PT xxx). The method used in this research is a qualitative approach, which allows researchers to gain an in-depth understanding of the challenges and factors that influence the implementation of taxation in companies. Primary data was obtained through in-depth interviews with the head of finance and financial staff who are responsible for withholding and reporting PPh 23. The research results show that delays in reporting and lack of coordination between internal units are the main obstacles in the tax withholding and reporting process. Apart from that, the unavailability of Exemption Certificates (SKB) from work partners also contributes to errors in tax deductions. This research recommends the need for increased communication and coordination with work partners as well as a better understanding of tax practices among staff to reduce risks related to tax compliance and improve the company's reputation. It is hoped that these findings will provide insight for companies in improving efficiency and compliance in the taxation process.